2017
DOI: 10.1103/physrevb.96.085410
|View full text |Cite
|
Sign up to set email alerts
|

Diagrammatic approach to orbital quantum impurities interacting with a many-particle environment

Abstract: Recently it was shown that an impurity exchanging orbital angular momentum with a surrounding bath can be described in terms of the angulon quasiparticle [Phys. Rev. Lett. 118, 095301 (2017)]. The angulon consists of a quantum rotor dressed by a many-particle field of boson excitations, and can be formed out of, for example, a molecule or a nonspherical atom in superfluid helium, or out of an electron coupled to lattice phonons or a Bose condensate. Here we develop an approach to the angulon based on the path-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 130 publications
(227 reference statements)
0
13
0
Order By: Relevance
“…The model tends to underestimate the line broadening by a few GHz, which we attribute to the fact that only single-phonon excitations are included into the ansatz (2). Using more involved, diagrammatic approaches [21] to the Hamiltonian (1) is expected to further improve the agreement. …”
Section: Matrix Elements For Spectroscopic Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model tends to underestimate the line broadening by a few GHz, which we attribute to the fact that only single-phonon excitations are included into the ansatz (2). Using more involved, diagrammatic approaches [21] to the Hamiltonian (1) is expected to further improve the agreement. …”
Section: Matrix Elements For Spectroscopic Transitionsmentioning
confidence: 99%
“…Recently, it was predicted that a superfluid can acquire angular momentum via a different, microscopic route, which takes effect in the presence of rotating impurities, such as molecules [6][7][8][9][10][11][12][13]. In particular, it was demonstrated that a rotating impurity immersed in a superfluid forms the 'angulon' quasiparticle, which can be thought of as a rigid rotor dressed by a cloud of superfluid excitations carrying angular momentum [14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…It can be easily generalized to analyze other far-from-equilibrium problems. A system closely related to the quantum impurity problem is the so-called angulon, i.e., a problem of rotational excitations of molecules immersed in a quantum fluid [86][87][88][89]. This system was shown to exhibit quasiparticles similar to polarons, but with a conserved total angular momentum and a cloud of angular excitations renormalizing the moments of inertia.…”
Section: Discussionmentioning
confidence: 99%
“…(2). They involve perturbations on the top of a microscopic deformation of the helium bath, i. e. an infinite number of bosonic excitations [25][26][27] . In the course of the paper, however, we aim to demonstrate that the solutions including up to triple excitations are able to catch changes in molecular spectra for broad range of species measured in helium.…”
Section: A the Angulon Hamiltonianmentioning
confidence: 99%